Necessary and Sufficient Conditions for Expressing Quadratic Rational Bézier Curves - Yang, Chaoyu; Yang, Jie; Liu, Ying; Geng, Xianya (Frontiers in Physics, 2020)
Quadratic rational Bézier curve transformation is widely used in the field of computational geometry. In this paper, we offer several important characteristics of the quadratic rational Bézier curve. More precisely, on the basis of proving its monotonicity, the necessary and sufficient conditions for transforming a quadratic rational Bézier curve into a point, line segment, parabola, elliptic arc, circular arc, and hyperbola are proved, respectively.